Kosmobraz jako narracja. Przypadek space docs koncernu BBC - Kempna-Pieniążek, Magdalena (Przestrzenie Teorii, 2025)
The article deals with the variability and dynamics of spacescapes understood as narratives encoded in cosmic views. Starting from the definition formulated by Alice Gorman, the author analyses three BBC series devoted to the exploration of the Solar System: The Planets (1999), Wonders of the Solar System (2010) and The Planets (2019), proving that spacescapes appear in all of them, but their roles differ. In The Planets from 1999, we encounter a narrative of technological sublimity; in Wonders of the Solar System – an Arcadian tale; and in the 2019 series – a narrative of terraforming other worlds. In the first part of the article, the author discusses selected issues of practices of space-making and studying cosmic landscapes. Then, using the example of three series produced by the BBC, she shows the dominant narratives embedded in the cosmogenic images present in contemporary high-budget space docs. Importantly, the narratives of technological sublimity, terraforming and Arcadianism are not mutually exclusive, but are closely related. In their evolution, they seem to follow the direction set by Gorman’s definition: while The Planets from 1999 primarily emphasise the ‘terrestrial’ elements of the vertical landscape, Wonders of the Solar System emphasise orbital shots in the style of The Blue Marble, and The Planets from 2019 show us places that have so far only been visited by unmanned space probes.